Interindividual differences in sympathetic and effector responses to arousal in humans - Donadio, Vincenzo (Blackwell Science Inc, 2002)
Surprising sensory stimuli have been found to attenuate one or two sympathetic discharges in human muscle nerves of some, but not all subjects, an effect suggested to be due to arousal. The aims of the present study were: (1) to provide evidence for or against an arousal mechanism by searching for evidence of habituation, and (2) to investigate if the presence or absence of inhibitory response is reproducible. To this end we recorded peroneal muscle sympathetic nerve activity (MSNA), electrocardiogram (ECG), finger blood pressure and changes of skin electrical resistance in 17 awake healthy subjects, while sensory stimuli consisting of five electrical pulses were delivered to a finger. The electrical pulses were triggered on five consecutive R waves of the ECG after a delay of 200 ms. Dummy stimuli, consisting of five trigger pulses without electrical pulses were used as controls, and the interval between two successive stimuli (real or dummy) was 30 s. On a group basis, the stimuli attenuated two initial and one late MSNA bursts. On an individual basis, significant attenuation of one or two initial bursts occurred in eight subjects, whereas in nine subjects there was no significant inhibition. In nine subjects the experiments were repeated once and in three subjects they were repeated twice. The effects on MSNA were reproducible in 11 of the12 subjects. In the group of subjects without significant MSNA inhibition the stimuli induced a small, transient increase in mean blood pressure, which was not present in the group with significant MSNA inhibition. Heart rate did not change in either group. In conclusion, the inhibitory effect on MSNA of five repeated electrical pulses to a finger is largely similar to that previously shown for one pulse, i.e. there is rapid habituation of the response, compatible with an arousal-induced effect. The inhibitory responsiveness shows marked interindividual differences, which are reproducible over several months and associated with different effects on blood pressure.